Tantangan Profesionalisme Guru Ekonomi Dalam Pembelajaran Pada Sekolah Menengah Atas/Sederajat di Era Revolusi Industri 4.0 - Masdianah, Masdianah (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2020)
The economics teacher as the frontline in implementing economic learning tasks in the classroom is able to display their professionalism which includes pedagogical, professional, social, and personality competencies by adapting the development of science and technology in the era of the industrial revolution 4.0. This paper aims to offer ideas about the economics teacher and the challenges of learning in the industrial era 4.0 marked by a leap in the progress of information and communication technology that has an impact on changes in all aspects including aspects of learning that demand to adapt to these new changes. Economics teachers must be able to absorb the latest information and phenomena, be able to utilize information and communication technology in learning, and be able to collaborate with students, colleagues, and education staff. Mastery and renewal of learning materials, learning innovations, social skills, and noble personal attitudes are actualized in learning tasks by adjusting to the demands of the industrial revolution era 4.0. Economics teachers as an integral part of other subject teachers, have professional responsibilities as well as moral responsibilities in preparing the nation's young generation who are intellectual-minded, behave-worthy of character, and skilled-skilled. Economics teachers need to make themselves creative, innovative teachers, and learning teachers; so that economics teachers are able to show their existence as a strong teacher in carrying out professionalism in the era of the industrial revolution 4.0.